2018
DOI: 10.1155/2018/2083121
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis in a Man as a Rare Source of Abdominal Pain: A Case Report and Review of the Literature

Abstract: Endometriosis occurs when a tissue resembling endometrial glands and stroma grows in ectopic sites, commonly causing infertility and pain. This condition is most often seen in women of reproductive age, involving pelvic sites such as the ovaries, broad ligaments, uterosacral ligaments, and posterior cul-de-sac. Very rarely, endometriosis has also been found in the lower genitourinary tract of men. A 40-year-old man presented to his primary care physician with abdominal pain. Further imaging discovered a midlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 14 publications
0
59
0
Order By: Relevance
“…As previously noted, Signorile et al [31] found CD10 positive remnants in the deep cul-de-sac only. Finally, Müllerian remnants or coelomic metaplasia in prostate and utricle may explain rare cases of endometriosis reported in males, after long-term high doses of estrogens for prostate carcinoma [36,37]. Immunohistochemical studies in men support both Müllerianosis and metaplasia theories [37].…”
Section: Theories On the Origin Of Endometriosismentioning
confidence: 99%
“…As previously noted, Signorile et al [31] found CD10 positive remnants in the deep cul-de-sac only. Finally, Müllerian remnants or coelomic metaplasia in prostate and utricle may explain rare cases of endometriosis reported in males, after long-term high doses of estrogens for prostate carcinoma [36,37]. Immunohistochemical studies in men support both Müllerianosis and metaplasia theories [37].…”
Section: Theories On the Origin Of Endometriosismentioning
confidence: 99%
“…While endometriosis and migraine appear to have clear-cut distinctions-anatomically, as well as in terms of clinical diagnosis and disease classification-some shared epidemiological characteristics or similarities suggest a comorbid relationship between them. For instance, similar to endometriosis, which almost exclusively affects women [12], migraine has a substantially higher prevalence in women (15%-18%) compared to men (6%), and women of reproductive age also experience a longer duration of migraine attacks with greater disability [13][14][15][16]. The two disorders share similar risk factors in women including early menarche, menorrhagia, and involvement of the menstrual cycle in their pathogenesis [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is most commonly a disease of women [3]. A total of 16 cases of endometriosis in males has been reported [4]. It occurs mostly in the pelvis [3].…”
Section: Discussionmentioning
confidence: 99%